2017
DOI: 10.1007/s00417-017-3656-3
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative robot assistant for vitreoretinal microsurgery: development of the RVRMS and feasibility studies in an animal model

Abstract: Maneuverability, accuracy and stability of robot-assisted vitreoretinal microsurgery using the RVRMS were demonstrated in this study. Wider application research of robotic surgery and improvement of a robotic system should be continued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…25 Two groups have developed telemanipulation systems comparable to the PSS. [26][27][28] They have shown successful application in animal studies, but they have yet to publish studies in human subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Two groups have developed telemanipulation systems comparable to the PSS. [26][27][28] They have shown successful application in animal studies, but they have yet to publish studies in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Another robot developed at the University of Leuven demonstrated that it was feasible and safe to inject ocriplasmin in the central retinal vein to treat retinal vein occlusion (RVO) in four patients using robot assistance 25 . Two groups have developed telemanipulation systems comparable to the PSS 26–28 . They have shown successful application in animal studies, but they have yet to publish studies in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to tremor removal and precise operation, new mechanisms or structures are explored to further improve RAMS. Snake-like robots have significant advantages to operate in the confined environment [105] , and are capturing more and more attention in recent years.…”
Section: Cooperative Controlmentioning
confidence: 99%
“…In breast A B reconstruction using the LD flap, the incision length is within 5 cm for endoscopic or robotic surgery; however, it is 15 cm or greater for conventional surgery. The advantage of endoscopic and robotic reconstructive breast surgery is quite clear, and the benefits are believed to be comparable to those of endoscopic or robotic abdominal surgery (9,10). If the incidence of other complications in endoscopic or roboticassisted mastectomy and immediate breast reconstruction with LD flap or silicone implant is not higher than that in conventional surgery, then it can be an excellent alternative that boosts patient satisfaction by minimizing scarring and postoperative pain.…”
Section: Serratus Ventralis Tricepsmentioning
confidence: 99%